Community-based assessment of marine resources contamination after a large-scale oil spill - CLÁUDIA HAMACHER; CÁSSIA O. FARIAS; MICHELLE P. ARAÚJO; JOÃO PEDRO M.P. PITTA; CARLOS ALBERTO P. DOS SANTOS; MÁRIO LUIZ GOMES SOARES (Anais da Academia Brasileira de Ciências, 2022)
Abstract As of August 2019, several oil slicks reached the Brazilian coast, compromising local ecosystems and the economy of coastal communities. In this context, this study aimed to assess seafood quality at the Canavieiras Extractive Reserve (RESEX), located in the state of Bahia, Northeastern Brazil, by determining polycyclic aromatic hydrocarbons (PAHs) concentrations in local biota following the oil spill. It was designed and carried out in a participatory manner, involving RESEX fishers, shellfish and crab gatherers and managers, as well as university researchers. A total of 72 biota samples were analyzed, and the sum of the 16 priority USEPA PAHs ranged from less than the limit of detection to 30.81 ng g-1 (w.w.). When also considering alkylated compounds, concentrations ranged from 3.53 to 360.75 ng g-1 (w.w.). No sample contained PAHs concentrations suggestive of human consumption risks. No difference in PAHs concentrations between the six studied areas and regarding different biota feeding habits were observed. Higher PAHs concentrations were generally noted in molluscs, as these organisms do not have enzyme systems capable of metabolizing these compounds. This initiative demonstrated the feasibility of participatory construction resulting in a study concerning valued species to local communities, ensuring a contribution to local fishing and marketing activities.